Selective downregulation of natural killer activating receptors on NK cells and upregulation of PD-1 expression on T cells in children with severe and/or recurrent Herpes simplex virus infections - Lenart, Marzena; Kluczewska, Anna; Szaflarska, Anna; Rutkowska-Zapała, Magdalena; Wąsik, Magdalena; Ziemiańska-Pięta, Anna; Kobylarz, Krzysztof; Pituch-Noworolska, Anna; Siedlar, Maciej (Immunobiology (1979), 2021)
•NK cells expressing activating receptors (CD16, NKp46, NKp80, NKG2D and 2B4) and/or expression of these receptors was selectively downregulated in children with severe and/or recurrent HSV infection;•NTB-A receptor expression was upregulated on patients’ CD16dimCD56bright NK cells and CD8+ T cell subsets;•HSV patients had increased percentage of CD4+ T cells expressing PD-1;•Two possible mechanisms promoting HSV infection - selective inhibition of activating receptors on NK cells, but not T cells, and upregulation of PD-1 on CD4+ T cells. Severe, recurrent or atypical Herpes simplex virus (HSV) infections are still posing clinical and diagnostic problem in clinical immunology facilities. However, the molecular background of this disorder is still unclear. The aim of this study was to investigate the expression of activating receptors on NK cells (CD16, NKp46, NKG2D, NKp80, 2B4, CD48 and NTB-A) and checkpoint molecule PD-1 on T lymphocytes and NK cells, in patients with severe and/or recurrent infections with HSV and age-matched healthy control subjects. As a result, we noticed that patients with severe and/or recurrent infection with HSV had significantly lower percentage of CD16brightCD56dim and higher percentage of CD16dimCD56bright NK cell subsets, when compared to control subjects, which may be associated with abnormal NK cell maturation during chronic HSV infection. Patients had also significantly downregulated expression of CD16 receptor on CD16bright NK cells. The expression of activating receptors was significantly reduced on patients’ NK cells - either both the percentage of NK cells expressing the receptor and MFI of its expression (NKp46, NKp80 and 2B4 on CD16brightCD56dim cells and NKp46 on CD16dimCD56bright cells) or only MFI (NKG2D on both NK cell subsets). It should be noted that the reduction of receptor expression was limited to NK cells, since there was no differences in the percentage of receptor-positive cells or MFI on T cells. However, NTB-A receptor was the only one which expression was not only simultaneously changed in patients’ NK and T cells, but also significantly upregulated on CD16dimCD56bright NK cell and CD8+ cell subsets. Patients had also upregulated proportion of CD4+ T cells expressing PD-1. Thus, we suggest that an increased percentage of PD-1+ cells may represent an independent indirect mechanism of downregulation of antiviral response, separate from the reduction of NK cell activating receptors expression. Altogether, our studies indicate two possible mechanisms which may promote perpetuation of HSV infection: 1) selective inhibition of activating receptors on NK cells, but not on T cells, and 2) upregulation of checkpoint molecule PD-1 on CD4+ T cells.